Avaliação a Serviço da Aprendizagem: Reflexões no Aperfeiçoamento das Práticas Pedagógicas de Professores de Química do Ensino Médio. - Silva, Eduarda de Sousa (Universidade Federal do Tocantins, 2024)
School evaluation should be understood as an auxiliary tool in directing teachers' pedagogical practices for the development of meaningful learning for students. In this sense, we mobilized the following research problem: how has evaluation in Chemistry teaching been used to direct pedagogical practice in High School? The present work sought to investigate how evaluation has been used to direct the pedagogical practices of high school Chemistry teachers. With this, we proposed to carry out a qualitative bibliographical review, seeking to analyze the Qualis Periodicals (A1-A4) present in the Sucupira Platform with a four-year evaluation from 2017-2020; the Annals of the National Chemistry Teaching Meeting (2006-2020) and the articles and works from events present in Google Scholar (2012-2022). As main results, we emphasize that the evaluation enables the teacher to understand, reflect, guide and innovate the pedagogical practices. In addition, it represents an opportunity for learning, identifying difficulties and regulating the teaching and learning process. Therefore, it allows us to realize that evaluation in Chemistry teaching can go beyond just assigning grades and certification of learning. Therefore, we recognize that evaluation has a role in guiding teachers in their pedagogical planning, directing improvements in the teaching-learning process.